Effectiveness of E-Modules for Physical Education, Sports and Health Subjects in Improving Learning Outcomes of Junior High School Students - Oksa Haryandi Gumara; Asep Sujana Wahyuri; Damrah Damrah; Nurul Ihsan (Universitas Muhammadiyah Enrekang, 2023)
This study aims to determine the effectiveness of E-modules in physical education sports and health subjects in improving the learning outcomes of junior high school students. This research is a type of Research and Development (R&D) research with the ADDIE model. The population in this study came from students of SMP Negeri 34 Kerinci. The research sample came from 2 classes, namely class VII B as an experimental class) and class VII C as a control class. The data collection technique is random sampling. The instruments used are tests and questionnaires. The data analysis technique is descriptive statistical analysis with the help of the SPSS version 21 application. The results showed a T-Test value of 0.00 <0.5. These findings explain that the development of e-modules is very effective in increasing student knowledge in physical education, sports , and health learning subjects. Furthermore, the development of this E-module helps students be more creative and innovative in learning